Boron- and nitrogen-doped photoluminescent polymer carbon nanoparticles as nanosensors for imaging detection of Cu2+ and biothiols in living cells. Issue 75 (9th October 2017) - Gao, Buhong; Zhao, Fengyi; Miao, Yingchun; Min, Huihua; Xu, Li; Huang, Chaobo
Abstract : Boron and nitrogen co-doped ellipsoidal polymer carbon nanoparticles-based nanoprobe for fluorescence detection and imaging of biothiols in biological samples. Abstract : Boron and nitrogen co-doped polymer carbon nanoparticles (BNPCNPs) were synthesized by a facile hydrothermal treatment using uric acid as a nitrogen source, and phenylboronic acid as a boron source for the first time. The nanoparticles with sizes in the range of 90 to 180 nm show excellent and stable fluorescence properties. Moreover, these BNPCNPs showed highly efficient fluorescence quenching ability in the presence of copper (Cu 2+ ) ions due to the formed nonfluorescent metal complexes via robust Cu 2+ –O or Cu 2+ –N interactions with the O and N of fluorescent BNPCNPs, which allowed the analysis of Cu 2+ ions in the range of 0.0033 to 80 μM. Besides Cu 2+ sensing, when biothiols were added, the quenched BNPCNPs-Cu 2+ system could be regained via the effective coordination/chelation interactions between Cu 2+ ions and the plentiful mercapto and amino groups of biothiols. In the light of this theory, simple biothiol sensors were fabricated without complicated, costly and time-consuming operations. The linear range and the limit of detection of the BNPCNPs-Cu 2+ system were 0.0078–80 μM and 2.1 nM for Lcy, 0.0085–85 μM and 2.7 nM for Hcy, and 0.013–89 μM and 4.2 nM for GSH, respectively. Especially, the nanoprobe exhibits good cell membrane permeability and excellent biocompatibility by HeLa cells assay, which is favorable for bioimaging applications. So this BNPCNPs probe can be further used for imaging of biothiols in living cells.